Effects of Li+ transport and intracellular binding on Li+/Mg2+ competition in bovine chromaffin cells - Fonseca, C. P. (2004)
Li+ transport, intracellular immobilisation and Li+/Mg2+ competition were studied in Li+-loaded bovine chromaffin cells. Li+ influx rate constants, ki, obtained by atomic absorption (AA) spectrophotometry, in control (without and with ouabain) and depolarising (without and with nitrendipine) conditions, showed that L-type voltage-sensitive Ca2+ channels have an important role in Li+ uptake under depolarising conditions. The Li+ influx apparent rate constant, kiapp, determined under control conditions by 7Li NMR spectroscopy with the cells immobilised and perfused, was much lower than the AA-determined value for the cells in suspension. Loading of cell suspensions with 15 mmol l-1 LiCl led, within 90 min, to a AA-measured total intracellular Li+ concentration, [Li+]iT=11.39±0.56 mmol (l cells)-1, very close to the steady state value. The intracellular Li+ T1/T2 ratio of 7Li NMR relaxation times of the Li+-loaded cells reflected a high degree of Li+ immobilisation in bovine chromaffin cells, similar to neuroblastoma, but larger than for lymphoblastoma and erythrocyte cells. A 52% increase in the intracellular free Mg2+ concentration, [Delta][Mg2+]f=0.27±0.05 mmol (l cells)-1 was measured for chromaffin cells loaded with the Mg2+-specific fluorescent probe furaptra, after 90-min loading with 15 mmol l-1 LiCl, using fluorescence spectroscopy, indicating significant displacement of Mg2+ by Li+ from its intracellular binding sites. Comparison with other cell types showed that the extent of intracellular Li+/Mg2+ competition at the same Li+ loading level depends on intracellular Li+ transport and immobilisation in a cell-specific manner, being maximal for neuroblastoma cells.